1981
DOI: 10.1136/bjsm.15.3.182
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Astrand-Ryhming nomogram for predicting maximal oxygen intake.

Abstract: The purpose of this study was to evaluate the validity of the predicted V02 max from the Astrand-Ryhming nomogram, using the cycle ergometer as the sole exercise mode and following the recommended submaximal test protocol. In addition, two sets of age correction factors were compared for accuracy. Using the Astrand age correction factors, the SEE of the predicted V02 max for the 40 male subjects was .42 L.mini1 or 5.7 ml.kg 1.minf1, (r = .76 and .83, respectively); there was no significant difference between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 5 publications
4
62
0
2
Order By: Relevance
“…If mean steady state heart rate (submaximal heart rate) at the end of the test was over 110 bpm, the test was ended. If the submaximal heart rate was below 110 bpm, the workload was increased, and the test continued for another 6 min, if tolerated by the participant (Cink and Thomas 1981). The Astrand nomogram was used to calculate physical fitness (in milliliter per kilogram per minute) from submaximal heart rate, workload, body mass, and gender (Astrand and Rodahl 1986).…”
Section: Physical Performancementioning
confidence: 99%
“…If mean steady state heart rate (submaximal heart rate) at the end of the test was over 110 bpm, the test was ended. If the submaximal heart rate was below 110 bpm, the workload was increased, and the test continued for another 6 min, if tolerated by the participant (Cink and Thomas 1981). The Astrand nomogram was used to calculate physical fitness (in milliliter per kilogram per minute) from submaximal heart rate, workload, body mass, and gender (Astrand and Rodahl 1986).…”
Section: Physical Performancementioning
confidence: 99%
“…For example, the Astrand cycle ergometer test is a simple steady state test lasting only 6 minutes, in which peak VO 2 is estimated using a simple nomogram. 7 For a review of other measures of aerobic capacity, the readers are referred to the Noonan and Dean 15 article. If therapists wish to conduct submaximal tests in a clinical setting, they are encouraged to follow ACSM standards, including maintaining strict emergency procedures.…”
Section: Baseline Exercise Testing For Aerobic Capacitymentioning
confidence: 99%
“…1) are represented by a third-order regression equation with two inflection points (high and low blood pressures). Previous studies 1,10) have shown that SBP during an exercise tolerance test increases slightly at a small intensity, there tends to increase rapidly when the exercise intensity rises above a certain level, but the increase is suppressed when the blood pressure is excessively elevated. This suppression of the increase is considered to be due to th e excitation of baroreceptors, which are enhanced to inhibit sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted VO 2 max was calculated from the regression line of load and HR and was calculated according to the formula 12.47 × physical work capacity (PWC) ÷ body weight (kg). PWC is defined as the exercise intensity at maximal heart rate 10,11) . This is one of the physical characteristics of the subjects.…”
Section: Measurement Indexmentioning
confidence: 99%